FACTORS RELATED TO RECEIVING COVID 19 VACCINATION IN THE PANCUR BATU AREA IN 2022 - Samuel Ginting; Felix Kasim; Jul Asdar Putra Samura (Fakultas Kesehatan Masyarakat Institut Kesehatan Medistra Lubuk Pakam, 2022)
Coronavirus 2019 is an infectious disease that occurs due to the corona virus 2 so that sufferers experience acute respiratory syndrome. Initially, this disease was detected in Wuhan, China in December 2019, and since then, it has spread throughout the world, resulting in the 2019-2020 coronavirus pandemic. The purpose of this study was to analyze the implementation of the covid 19 vaccine which included: knowledge, attitudes, actions, distance to health centers and health facilities with the provision of covid 19 vaccination in Pancur Batu District. Quantitative research was selected using a survey method through a Cross Sectional Study approach. The results obtained are that there is a relationship between knowledge and acceptance of vaccination with a p-value of 0.003. In addition, there is also a relationship between action and vaccination receipts with a p-value of 0.000 and a relationship between health facilities and the acceptance of COVID-19 vaccination with a p-value of 0.000 in Pancur Batu District in 2022.